Linking organizational crises and reactive strategies via dimensions of legitimacy - Heiko Breitsohl (University of Wuppertal, Schumpeter School of Business and Economics, 2009)
Research on organizational crises has typically focused on case studies or measures for crisis prevention, while the social dimension of crises has remained largely unexplored. In some rare exceptions, differences in the efficacy of reactive strategies depending on the type of crisis have been reported. However, the mechanisms behind these differences remain unclear. This paper aims to fill this gap by arguing that organizational crises and effective reactions are linked by different dimensions of legitimacy perceived by stakeholders. To this end, after elaborating on the role of legitimacy in organizational crises, typologies of crises as well as reactive strategies are presented, accompanied by propositions about possible links.
urn:nbn:de:hbz:468-20090593
Keywords: 330; Krisenmanagement; Organisation; Organisatorischer Wandel; Stakeholder